(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper is a review of the structural causes and triggers of the first major international financial crisis of the XXI century, and shows a comparison respect to previous financial crises. It is proposed a review of the issues that led to the loss of confidence in the system, raising some basic ideas for the changes in the international financial system causing a sustainable recovery in time, as a basis for value creation based on fundamentals and reasonable expectations for companies, assets and financial agents.